2012
DOI: 10.1039/c2sm25864a
|View full text |Cite
|
Sign up to set email alerts
|

Induced dye leakage by PAMAM G6 does not imply dendrimer entry into vesicle lumen

Abstract: Dendrimers are polymers with unique properties that make them promising in a variety of applications such as potential drug and gene delivery systems. Polyamidoamine (PAMAM) dendrimers, in particular, have been widely investigated since they enter rapidly into cells. The entry mechanism, however, is still not yet fully clarified as both passive and active uptake have been proposed. In this work we focus on understanding passive uptake, for which simple cell model systems are used in order to ensure that only d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 63 publications
4
36
0
Order By: Relevance
“…The domains containing more dendrimers should have more significant change in the molecular packing of surrounding lipids. Åkesson et al got similar results when investigating giant liposomes by fluorescent microscopy [27].…”
Section: Changes In Thermal Behaviormentioning
confidence: 63%
See 1 more Smart Citation
“…The domains containing more dendrimers should have more significant change in the molecular packing of surrounding lipids. Åkesson et al got similar results when investigating giant liposomes by fluorescent microscopy [27].…”
Section: Changes In Thermal Behaviormentioning
confidence: 63%
“…They showed that dendrimers attach to the surface of the vesicles and can bridge neighboring vesicles until liposomes collapse in lamellar phase in which dendrimers are located between the layers. Later they investigated the effect of dendrimers on giant unilamellar vesicles (GUVs) by fluorescent microscopy and on supported lipid bilayers by quartz crystal microbalance with dissipation monitoring (QCM-D) and neutron reflectivity [27][28][29]. Interestingly they have found that the dendrimers enhance the permeability of the membranes for small molecules without hole formation or passive translocation across the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…6 Although passive and endocytosis pathways have been proposed, the exact mechanism of the transport process is only partially understood. 7 In cells, dendrimers can interact with biomembranes, such as the membrane of an endosome (membrane-bounded compartment inside cells) 8 and a cell membrane. 9,10 Therefore, interactions between PAMAM dendrimers and biomembranes at different transport stages should be understood.…”
Section: Introductionmentioning
confidence: 99%
“…The vesicles were immobilized on the coverslip surface via an adapted biotin-streptavidin binding procedure [37,38] (Fig. 1d), which is described in more detail in the SI [33].…”
Section: Vesicle Preparationmentioning
confidence: 99%